The Improvement Of Debris Index And Knowledge Through Dental Health E-Book Program For Elementary School Students In Jakarta And Bali - Kristianto, Jusuf; Cahyati, Widya Hary; Yulita, Ita; Dwiastuti, Sagung Agung Putri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Riskesdas 2018 show that the largest percentage of dental problems in Indonesia is dental caries (45.3%). The provision of dental health services in school is carried out through UKGS. Counseling method and tooth brushing demonstrations to promote dental health are routinely carried out for elementary school students. This method is used to change the behavior of maintaining dental health by brushing teeth properly and correctly. With current technological developments, the use of Android is common in learning activities. Android applications can be media that is favored by children. The educational program named